Kajian Yuridis Multidimensi: Mengatasi Tantangan Eksploitasi Anak dan Mengembangkan Solusi Hukum Adaptif - Mushsinulkhair FR, Muh. Farhan; Rahman, Muhammad Sabir; Asba, Patahillah; Darwis, Muhammad (Jurnal Litigasi Amsir, 2024)
The results of the study showed that the factors that led to the exploitation of children in Parepare City were economic, low education from parents, and lack of education related to exploitation issues, which caused parents not to know that if a minor was employed it would already be included in the realm of a crime even though it was their child, and another factor was the general public’s lack of awareness in reporting child exploitation. 35 of 2014 concerning Child Protection which reads "Everyone who violates the provisions referred to in article 76I, shall be punished with imprisonment for a maximum of 10 (ten) years and/or a fine of up to Rp. 2000.000.000.00, (Two Hundred Million Rupiah).